Make your brand matter : experience-driven solutions to capture customers and keep them loyal - Soechtig, Steven G. (John Wiley & Sons, Inc., 2022)
"Historically, consumer and B2B companies have made significant investments in defining and maintaining their brand identity. They worked to establish their brand promise, perception, and voice, establishing market positioning and differentiation to attract specific buying demographics. Once established, these companies would train their employees to project and reinforce that brand identity at every step of the customer journey, from initial awareness through evaluation, transaction, servicing, and loyalty. The brand defined the experience, and the experience reinforced the brand. The digital era disrupted this traditional brand management model. As consumers and business buyers rapidly shifted to online channels, new methods of engagement emerged, and buyers were suddenly entering the engagement cycle at different points. While brand marketers and managers continued to reinforce their traditional brand positioning, digital teams scrambled to create new engagement experiences to meet the evolving demands of the customer. Platforms, tools and technologies were implemented for function first, and then were retrofitted in an attempt to reflect the brand positioning and promise. The result was a disconnect between brand and experience, which led to confusion and frustration for many customers expecting to receive a consistent representation regardless of channel"--